ChemInform Abstract: Mixed‐Valent NaCu4Se3: A Two‐Dimensional Metal. Issue 30 (7th July 2016) - Sturza, Mihai; Bugaris, Daniel E.; Malliakas, Christos D.; Han, Fei; Chung, Duck Young; Kanatzidis, Mercouri G.
Abstract: The new title compound is synthesized in quantitative yield by solid state reaction of a stoichiometric mixture of CuSe, Cu2 Se, and Na (alumina crucible, 800 °C, 24 h, followed by annealing at 600 °C for 3 d).